2021
DOI: 10.2147/oarrr.s318810
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Demographics, Disease Activity, Disability, and Treatment Among Rheumatoid Arthritis Patients with and without Osteoporosis

Abstract: Introduction Osteoporosis (OP) is one of the most common comorbidities associated with rheumatoid arthritis (RA). Literatures reported that the risk for developing OP was strongly associated with duration and severity of RA. We aim to elaborate on the consequences of OP on disease activity and management plan in patients with RA. Patients and Methods A retrospective cohort study recruited 408 patients, including those with RA alone and with RA plus OP. The RA disease ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The relation of disease activity to osteoporosis was investigated in a relatively high number of studies. Although neutral data were also published [ 46 ], the vast majority of reports found that in RA a higher disease activity is associated with bone loss and/or osteoporosis [ 47 , 48 , 49 , 50 ]. Indirectly, this association underlines the important role of the immunological disease process for systemic bone alterations in RA.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…The relation of disease activity to osteoporosis was investigated in a relatively high number of studies. Although neutral data were also published [ 46 ], the vast majority of reports found that in RA a higher disease activity is associated with bone loss and/or osteoporosis [ 47 , 48 , 49 , 50 ]. Indirectly, this association underlines the important role of the immunological disease process for systemic bone alterations in RA.…”
Section: Human Association Studiesmentioning
confidence: 99%
“…Ankylosing spondylitis [99], RA [100], SLE [101] Neurological and musculoskeletal risk factors Epilepsy [102,103], Multiple sclerosis [104], Muscular dystrophy [105], Parkinson's disease [106], Spinal cord injury [107,108], Stroke [109] Miscellaneous conditions and diseases Addiction to narcotics [110], AIDS/HIV [111,112], Amyloidosis [113], Chronic metabolic acidosis, COPD [114], CHF [115], Endstage renal disease [116], Hypercalciuria [117], Idiopathic scoliosis [118], post-transplant bone disease [119], Socioeconomic status [120], Sarcoidosis [121], Weight loss [122] Long-term calcium intake is essential in building bone reserves before the PBM level and maintaining bone mass later at age twenty. The risk of secondary OP can be initiated by calcium deficiency [123] or lack of absorption [124].…”
Section: Rheumatologic and Autoimmune Diseasesmentioning
confidence: 99%